SOCIOLINGUISTIC REFLECTIONS IN THE USE OF DETERMINERS IN ESL AND EFL: THE EDUCATED NIGERIAN ENGLISH (ENE) EXAMPLES - Omowumi Bode Steve Ekundayo (Universitas Kuningan, 2017)
This paper examines the use of English articles and some determiners in English as second language (ESL) with a view to establish the differences between ESL and native English use of determiners and the sociolinguistic factors that inform their use. Examples were drawn from Educated Nigerian English (ENE) and Standard British English (SBE). The paper is based on the concepts of linguistic interference and intraference. Observation and recording of spontaneous speeches, secondary sources, the Internet and questionnaire were used to gather data from 2005 to 2014 across Nigeria to establish how determiners are deployed and the currency and ubiquity of the patterns observed in ENE. The responses to the questionnaire and interviews were analyzed and presented in simple percentile, frequency tables and charts, and discussed thereafter. The study discovered that there are clear differences in the patterns of the use of articles in ESL, as the ENE examples show. As a result of interference and intraference, educated Nigerians tend to overgeneralize the use of articles and determiners with noun phrases, applying them superfluously or omitting them where necessary and even sometimes using the as a possessive determiner for his, her and their. They also often yoke similar and exclusive determiners together in nominal structures. The paper concludes that these patterns should be treated as some of the features that characterize Nigerian English syntax.